Diverse Bacteria with Lignin Degrading Potentials Isolated from Two Ranks of Coal - Wang, Lu; Nie, Yong; Tang, Yue-Qin; Song, Xin-Min; Cao, Kun; Sun, Li-Zhu; Wang, Zhi-Jian; Wu, Xiao-Lei (Frontiers in Microbiology, 2016)
Taking natural coal as a “seed bank” of bacterial strains able to degrade lignin that is with molecular structure similar to coal components, we isolated 393 and 483 bacterial strains from a meager lean coal sample from Hancheng coalbed and a brown coal sample from Bayannaoer coalbed, respectively by using different media. Statistical analysis showed that isolates were significantly more site-specific than medium-specific. Of the 876 strains belonging to 27 genera in Actinobacteria, Firmicutes, and Proteobacteria, 612 were positive for lignin degradation function, including 218 strains belonging to 35 species in Hancheng and 394 strains belonging to 19 species in Zhongqi. Among them, the dominant lignin-degrading strains were Thauera (Hancheng), Arthrobacter (Zhongqi) and Rhizobium (both). The genes encoding the laccases- or laccase-like multicopper oxidases, key enzymes in lignin production and degradation, were detected in three genera including Massilia for the first time, which was in high expression by real time PCR (qRT-PCR) detection, confirming coal as a good seed bank.